The fatigue strength of transverse fillet welded joints a study of the influence of joint geometry - Gurney, T. R. (Woodhead Publishing series in welding and other joining technologies, 1991)
This report is the result of a major study on the influence of both main plate thickness and of attachment size on the fatigue strength of joints with transverse non-load-carrying fillet welds. In particular, it defines the extent to which the size of the attachment might influence the thickness effect in such joints. Through a whole range of different tests, the study confirms that the present thickness effect correction for certain types of joint is too severe